Cadres théoriques mobilisant les concepts de résilience et de vulnérabilité - Pauline Buchheit; Patrick d’Aquino; Olivier Ducourtieux (VertigO)
The concepts of resilience and vulnerability have been used in different disciplines to analyze and manage the dynamics of geographical areas and social groups facing rapid and uncertain changes. Both concepts are used within a variety of frameworks of analysis of society-environment relationships. This article aims to review the different analytical frameworks and their respective contributions to the analysis of the interactions between social and ecological dynamics. While all reviewed frameworks take into account the interactions of individuals with their environment, they do not, however, assess the vulnerability and resilience at the same scales. In particular, some frameworks are actor-centered, while others are system-centered. We propose a framework which reconciles these two approaches. This framework considers a socioecosystem both as a specific representation of the environment offered by a stakeholder, and as a set of elements contributing to one final function, and organized in a hierarchy of levels of observation, in which each level corresponds to an intermediary function. We propose a participatory approach to confront the systemic representations that have been built by different actors about their environment, and in particular to confront the functions that have been assigned within these representations to the different levels of observation. This process is not intended to lead to a shared vision of an area and its functions, but rather to discuss the potential complementarity of the issues and stakes presented by different actors, before any further assessment of the vulnerability and resilience of the study area to specific changes.